ANALISIS EFEKTIVITAS MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN PENDEKATAN ANALISIS SWOT SEKOLAH DASAR TRI MURTI DENPASAR - Melia Melani, Made; Sita Pramaswari, Dewa Ayu; Chindytia; Surya Abadi, Ida Bagus Gede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of School-Based Management (SBM) in improving the quality of education through a SWOT analysis approach at SD Tri Murti Denpasar. The research was motivated by the importance of effective school management in supporting educational quality improvement amid increasingly dynamic educational developments and demands. This study employed a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, documentation, and questionnaires involving the principal, teachers, and school stakeholders. The collected data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings revealed that the implementation of School-Based Management at SD Tri Murti Denpasar was categorized as “Good” with a score of 80. The school demonstrated strengths in principal leadership, teacher involvement in school programs, adequate learning facilities, and the utilization of digital learning media. The SWOT analysis results also indicated that the school possesses strong potential to improve educational quality through the support of technological developments and community participation. However, several aspects still require improvement, particularly in program evaluation, administrative management, and stakeholder coordination. Therefore, continuous development strategies are necessary to optimize the effectiveness of School-Based Management and support sustainable educational quality improvement at the school.